Kepraktisan e-Modul Fisika Berbasis Discovery Learning Berbantuan Aplikasi 3D Pageflip Professional pada Materi Gelombang Berjalan dan Gelombang Stasioner - Reno Ali Afan; Ovilia Putri Utami Gumay; Endang Lovisia (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2023)
This study aims to develop a physics E- Module based on Discovery Learning assisted by the 3D PageFlip Professional application on practical moving wave and stationary wave material. This research is an R&D (Research and Development) development research using a 4D development model consisting of Define, Design, Development, and Disseminate. At the development stage there is a practicality test and the research subjects are physics teachers and students. The data collection technique uses a questionnaire that is distributed during the practicality test. The practicality test results that have been obtained are 92% for the physics teacher practicality trial with very practical criteria, a practicality score of 87% is obtained for the limited group practicality trial with very practical criteria, and a practicality score is 83% for the large group trial. with very practical criteria. So it can be concluded that the E- Module physics based on Discovery Learning assisted by the 3D PageFlip Professional application on traveling wave and stationary wave material through a practicality test using a questionnaire instrument.